UX for dummies - Chesnut, Donald; Nichols, Kevin (West Sussex, England : John Wiley & Sons, Ltd, 2014)
If you want to learn the tools and techniques necessary for effective user experience (UX) design, this guide will help you apply strategies that align with your business goals.
Getting started with UX. Defining UX and the process ; Examining why you should use UX ; Determining your users ; Modeling the experience ; Understanding UX as (R)evolution -- Components of design. Taming the beast: understanding what you do and don't have ; Developing content strategy ; Designing the content strategy ; Building the information architecture ; Designing for specific channels ; Diving into visual design -- Your UX in action. Testing: how it can save your UX ; Measuring your UX to keep it relevant ; Making it past the finish line -- The part of tens. Ten reasons why the user is your most important consideration ; Ten ways to ensure that your UX is best in class ; Ten UX principles that never change.
Keywords: User interfaces (Computer systems).; User-centered system design; Web sites -- Design; Human-computer interaction; Human-computer interaction; User-centered system design; User interfaces (Computer systems); Web sites -- Design; Benutzeroberflhe; Webdesign; Mensch-Maschine-Kommunikation.